Exercise improves cardiac fibrosis by stimulating the release of endothelial progenitor cell-derived exosomes and upregulating miR-126 expression - Fu, Genzhuo; Wang, Zhao; Hu, Siyuan (Frontiers in Cardiovascular Medicine, 2024)
Cardiac fibrosis is an important pathological manifestation of various cardiac diseases such as hypertension, coronary heart disease, and cardiomyopathy, and it is also a key link in heart failure. Previous studies have confirmed that exercise can enhance cardiac function and improve cardiac fibrosis, but the molecular target is still unclear. In this review, we introduce the important role of miR-126 in cardiac protection, and find that it can regulate TGF-β/Smad3 signaling pathway, inhibit cardiac fibroblasts transdifferentiation, and reduce the production of collagen fibers. Recent studies have shown that exosomes secreted by cells can play a specific role through intercellular communication through the microRNAs carried by exosomes. Cardiac endothelial progenitor cell-derived exosomes (EPC-Exos) carry miR-126, and exercise training can not only enhance the release of exosomes, but also up-regulate the expression of miR-126. Therefore, through derivation and analysis, it is believed that exercise can inhibit TGF-β/Smad3 signaling pathway by up-regulating the expression of miR-126 in EPC-Exos, thereby weakening the transdifferentiation of cardiac fibroblasts into myofibroblasts. This review summarizes the specific pathways of exercise to improve cardiac fibrosis by regulating exosomes, which provides new ideas for exercise to promote cardiovascular health.